2018
DOI: 10.1158/1078-0432.ccr-17-3713
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis Identifies Therapeutic Biomarkers in Inflammatory Bowel Disease–Associated Colorectal Cancers

Abstract: Inflammatory bowel disease-associated colorectal cancers (IBD-CRC) are associated with a higher mortality than sporadic colorectal cancers. The poorly defined molecular pathogenesis of IBD-CRCs limits development of effective prevention, detection, and treatment strategies. We aimed to identify biomarkers using whole-exome sequencing of IBD-CRCs to guide individualized management. Whole-exome sequencing was performed on 34 formalin-fixed paraffin-embedded primary IBD-CRCs and 31 matched normal lymph nodes. Com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…Our genetic profiling of UC-CRC development confirmed TP53 mutations as a key event of chronic inflammation-driven colorectal carcinogenesis occurring in 87% (20 of 23) of UC-CRC samples. This is in concordance with previous next generation sequencing based publications reporting TP53 mutation frequencies in UC-CRC of 57% (n = 7) ( 15 ), 63% (n = 16) ( 16 ), 53% (n = 15) ( 17 ), and 86% (n = 29) ( 18 ), respectively. Comparable TP53 mutation frequencies have also been observed in CD-CRC with 100% (n = 3) ( 15 ), 88% (n = 8) ( 16 ), 76% (n = 29) ( 39 ), 69% (n = 13) ( 17 ) and 94% (n = 18) ( 18 ), respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our genetic profiling of UC-CRC development confirmed TP53 mutations as a key event of chronic inflammation-driven colorectal carcinogenesis occurring in 87% (20 of 23) of UC-CRC samples. This is in concordance with previous next generation sequencing based publications reporting TP53 mutation frequencies in UC-CRC of 57% (n = 7) ( 15 ), 63% (n = 16) ( 16 ), 53% (n = 15) ( 17 ), and 86% (n = 29) ( 18 ), respectively. Comparable TP53 mutation frequencies have also been observed in CD-CRC with 100% (n = 3) ( 15 ), 88% (n = 8) ( 16 ), 76% (n = 29) ( 39 ), 69% (n = 13) ( 17 ) and 94% (n = 18) ( 18 ), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…This is in concordance with previous next generation sequencing based publications reporting TP53 mutation frequencies in UC-CRC of 57% (n = 7) ( 15 ), 63% (n = 16) ( 16 ), 53% (n = 15) ( 17 ), and 86% (n = 29) ( 18 ), respectively. Comparable TP53 mutation frequencies have also been observed in CD-CRC with 100% (n = 3) ( 15 ), 88% (n = 8) ( 16 ), 76% (n = 29) ( 39 ), 69% (n = 13) ( 17 ) and 94% (n = 18) ( 18 ), respectively. Mutations in other genes were infrequent in both UC-CRC and CD-CRC.…”
Section: Discussionmentioning
confidence: 83%
“…SBS32, however, would only be expected in patients receiving purine therapy and so would not be present in sporadic colorectal cancers. These signatures have also not been reported in studies of colitis-associated colorectal cancers but this is likely due to a relative lack of power due to the small number of sequenced exomes ( Robles et al., 2016 ; Baker et al., 2019 ; Din et al., 2018 ).
Figure S3 Phylogenetic Trees for All Crohn’s Disease Patients, Related to Figures 2 , 4 , and 6 Mutational signatures are overlaid on the trees and putative driver mutations are mapped to the branch in which they occur.
…”
Section: Resultsmentioning
confidence: 92%
“…Epidemiological research has also shown that antibiotics over-scavenge the gut flora, causing macrophages to overreact to bacteria, thereby disrupting oxidative phosphorylation. Hypermutation occurs in 27% of IBD-associated colorectal cancer cases, including DNA repair dysfunction ( Din et al, 2018 ). Lipopolysaccharide isolated from Helicobacter disrupts intestinal DNA repair, increasing the risk of permanent genotoxic effects, contributing to IBD or colon cancer ( Cavallo et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%